Moving the goalposts: addressing limited overlap in estimation of average treatment effects by changing the estimand - Richard K. Crump; V. Joseph Hotz; Guido W. Imbens; Oscar A. Mitnik (Institute for the Study of Labor (IZA), 2006)
Estimation of average treatment effects under unconfoundedness or exogenous treatment assignment is often hampered by lack of overlap in the covariate distributions. This lack of overlap can lead to imprecise estimates and can make commonly used estimators sensitive to the choice of specification. In such cases researchers have often used informal methods for trimming the sample. In this paper we develop a systematic approach to addressing such lack of overlap. We characterize optimal subsamples for which the average treatment effect can be estimated most precisely, as well as optimally weighted average treatment effects. Under some conditions the optimal selection rules depend solely on the propensity score. For a wide range of distributions a good approximation to the optimal rule is provided by the simple selection rule to drop all units with estimated propensity scores outside the range [0.1, 0.9].
urn:nbn:de:101:1-20090626111
Keywords: 330; Mikroökonometrie; Schätztheorie; Statistische Verteilung; Theorie